(untitled) (Journal of Nepal Geological Society, 2001)
The Arun Valley can be divided into the Upper Arun Periglacial Valley (UAPV) and Lower Arun Fluvial Valley (LAFV). The area separated by the linearly arranged ridges of Jaljale Danda, Harale Danda, and Sichok Danda. The UAPV lies in the north whereas the LAFV occupies the southern territories. The UAPV is further divided into four geomorphic provinces with fifteen distinct Holocene terrace levels, whereas the LAFV is divided into four geomorphic provinces with thirteen Pleistocene terrace levels. The concept of geomorphic province is introduced to denote distinct geomorphological features formed in a type locality within a given geological time span. The identified geomorphic surfaces are morpho-stratigraphically defined at respective villages and have a wide geographic distribution. This paper attempts to classify geomorphologically the whole Arun watershed and to compare the position of various terraces in terms of neo-tectonic activities. The main geomorphic features of the watershed and their relationship with the major geological structures are also discussed. The boundaries of the geomorphic province often coincide with the reported thrusts in the area.